[Spinal intradural tumors] - Struffert, T; Grunwald, I; Roth, C; Reith, W (2004)
Spinal intradural tumors are uncommon lesions but may cause significant morbidity. In establishing the differential diagnosis for a spinal lesion, location, age, and the patient's clinical presentation are important. Magnetic resonance imaging plays a central role in the visualization of spinal tumors, easily allowing tumors to be classified as extradural, intradural extramedullary, or intramedullary which is very useful in tumor characterization. We describe intradural tumors; the majority is extramedullary, with nerve sheath tumors being the most frequent. Intramedullary tumors are uncommon spinal tumors. Ependymomas and astrocytomas comprise the majority of this group. Typical imaging features of both intradural extramedullary and intramedullary tumors are described.